2016
DOI: 10.1136/sextrans-2015-052354
|View full text |Cite
|
Sign up to set email alerts
|

How do HIV-negative individuals in sub-Saharan Africa change their sexual risk behaviour upon learning their serostatus? A systematic review

Abstract: ObjectiveTo determine whether, and how, sexual behaviour of HIV-negative individuals in sub-Saharan Africa (SSA) changes upon learning their serostatus.MethodsWe systematically reviewed the published literature using EMBASE and Medline to search for publications between 2004 and 2014. We included studies that quantified behaviour change (condom use, number of sexual partners or sex acts) following an HIV test in HIV-negative adults in SSA, and extracted relevant data including study characteristics and measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The majority of participants in this study learned their study partner was living with HIV a month or less than a month before they initiated PrEP, which may have also contributed to the observed decrease in HIV risk-related sexual behaviors within heterosexual HIV serodiscordant couples in the month following PrEP initiation. HIV serodiscordant couples face a fragile period in their relationship when they learn their discordant diagnosis and often change their sexual behaviors in response to this knowledge [32,33]. In this study, it was difficult for us to disentangle the association between knowledge among participants of their study partner's HIV-positive status on HIV risk-related sexual behaviors from that of PrEP initiation on HIV risk-related sexual behaviors because often these two events happened very close to one another.…”
Section: Discussionmentioning
confidence: 93%
“…The majority of participants in this study learned their study partner was living with HIV a month or less than a month before they initiated PrEP, which may have also contributed to the observed decrease in HIV risk-related sexual behaviors within heterosexual HIV serodiscordant couples in the month following PrEP initiation. HIV serodiscordant couples face a fragile period in their relationship when they learn their discordant diagnosis and often change their sexual behaviors in response to this knowledge [32,33]. In this study, it was difficult for us to disentangle the association between knowledge among participants of their study partner's HIV-positive status on HIV risk-related sexual behaviors from that of PrEP initiation on HIV risk-related sexual behaviors because often these two events happened very close to one another.…”
Section: Discussionmentioning
confidence: 93%
“…[32] However, a systematic review on the behavioral impact of finding out one’s own HIV-negative serostatus in sub-Saharan Africa concluded that, with the exception of serodiscordant couples, there is variable evidence that awareness of one's HIV-negative serostatus leads to substantial changes in risk behavior. [33] Data on the potential behavioral effect of repeat testing and counseling in postpartum women are lacking. We hypothesized that: 1) extended repeat HIV testing and enhanced counseling during late pregnancy and throughout breastfeeding can increase and sustain risk reduction behaviors and prevent incident sexually transmitted infections (STI) and HIV infections among HIV-uninfected pregnant and lactating women, and 2) that enhanced couple counseling can further enhance this effect through improved couple communication and emotional and economic support from male partners.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found only a moderate positive influence on risky sexual behaviour following access to HTS [12], with others indicating no impact on risky sexual behaviour following utilisation of HTS [11]. There is evidence that clinician-delivered counselling is effective in reducing unprotected sex among people testing positive for HIV [13], whilst further studies have revealed no impact for individuals testing HIV negative [18]. A further study has revealed that exposure to HTS (compared to non-exposure) was associated with a 41% reduction in the hazard of HIV acquisition among youth in KwaZulu-Natal over 4.5 years [19].…”
Section: Introductionmentioning
confidence: 99%